The Mediamorphosis of Aula Magazine: Islam Nusantara Media and Postcolonial Resistance in the Digital Era - Lukman Hakim; Ellyda Retpitasari (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This study analyzed the mediamorphosis of Aula Magazine from a postcolonial perspective to examine how an Islam Nusantara media outlet maintained its existence, cultural identity, and epistemic autonomy amid the hegemony of global digital media. Mediamorphosis was conceptualized as a process of negotiating the epistemic position of local Islamic media within a digital landscape dominated by Western media values and knowledge structures. A qualitative approach with a constructivist paradigm was employed. Data were collected through interviews with key participants and documentation of Aula Magazine’s transformation and were analyzed inductively to identify the strategic dimensions of mediamorphosis. The findings indicated that Aula implemented three main strategies. First, co-evolution was achieved by expanding its presence across digital platforms and social media to create alternative spaces for Islamic discourse. Second, convergence was realized through the development of the majalahaula.id news portal, which integrated journalism, da’wah, and Islam Nusantara perspectives. Third, complexity was reflected in audience participation, contributor engagement, and content designed to attract younger readers. These strategies demonstrated that Aula’s mediamorphosis not only sustained its institutional existence but also functioned as symbolic resistance to digital colonialism by preserving and disseminating Indonesian Islamic knowledge. The study’s novelty lay in interpreting mediamorphosis as a strategy for both symbolic resistance and epistemic survival.